MECHANISTIC EVALUATION OF LIME-MODIFIED ASPHALT CONCRETE MIXTURES (Journal of Engineering, 2011)
Frequently, Load associated mode of failure (rutting and fatigue) as well as, occasionally, moisture damage in some sections poorly drained are the main failure types found in some of the newly constructed road within Baghdad as well as other cities in Iraq. The use of hydrated lime in pavement construction could be one of the possible steps taken in the direction of improving pavement performance and meeting the required standards. In this study, the mechanistic properties of asphalt concrete mixes modified with hydrated lime as a partial replacement of limestone dust mineral filler were evaluated. Seven replacement rates were used; 0,0.5, 1, 1.5, 2, 2.5 and 3 percent by weight of aggregate. Asphalt concrete mixes were prepared at their optimum asphalt content and then tested to evaluate their engineering properties which include moisture damage, resilient modulus, permanent deformation and fatigue characteristics. These properties have been evaluated using indirect tensile strength, uniaxial repeated loading and repeated flexural beam tests. Mixes modified with hydrated lime were found to have improved fatigue and permanent deformation characteristics, also showed lower moisture susceptibility and high resilient modulus. The use of 2 percent hydrated lime as a partial replacement of mineral filler has added to local knowledge the ability to produce more durable asphalt concrete mixtures with better serviceability.